Detection of White Spot Virus in Penaeus monodon and Metapenaeus dalli from Hagonoy, Bulacan - Alenton, Rod Russel R.; Aniag, Anna Dominique M.; Bulaong, Maria Veronica G.; Reblando, Geormae Anne K.; Urayenza, Annie Grace V.; Yasuda, Jean Kathleen V.; Maningas, Mary Beth B. (2011)
Shrimp aquaculture is an integral source of revenue in developing tropical countries in Southeast Asia such as the Philippines. In the early 1990s, the country ranked 3rd in the shrimp international market, however the industry slid back to the 13th as it is presently plagued with outbreaks of diseases which causes massive decrease of production. Among these diseases, White Spot Virus (WSV) remains one of the most potent and infectious for most knows species of cultivated penaeid shrimps. It is in this light that the presence of White Spot Virus (WSV) in Penaeus monodon and Metapenaeus dalli, both species were collected in three commercial ponds in Hagonoy, Bulacan. In every sampling site, five shrimps of each species were collected, and from each shrimp tissue samples from gills, hemolymph, heart and hepatopancreas were obtained. DNA were then extracted from each organ and were used in the detection through Polymerase Chain Reaction (PCR) amplification. Elongation factor 1-alpha (EFI-α), primers was used to check DNA integrity and as an internal control. Only the hemocyte samples yielded positive among all the tissues tested. Hence, hemocyte was utilized in all 30 samples. Twenty percent (20%) of the sampled tissues of P. monodon shrimps were found to be positive. However, M. dalli shrimps from the same sampling sites were all found negative from WSV. These results, coupled with the fact that both species were collected from the same pond, suggest that M. dalli is more resistant to WSV compared to P. monodon.
Keywords: Shrimp culture; Metapenaeus; Shrimps -- Diseases